Mesograzer identity, not host algae, determines consumer stable isotope ratios. Issue 2 (7th February 2016) - Nordström, Marie C.; Aarnio, Katri; Bonsdorff, Erik
ABSTRACT: Species-specific foraging habits or feeding preferences influence the overall trophic functioning in consumer assemblages. We set out to assess the in situ trophic diversity in a mesograzer assemblage (isopods, amphipods and gastropods) associated with marine littoral macroalgae. More specifically, we set out to establish whether stable isotope ratios of carbon (δ 13 C) and nitrogen (δ 15 N) are dependent on primary consumer identity or expressed in relation to the identity of the algal host, i.e . the habitat of the consumer. Consumer locations in bivariate isotope space revealed significant differences among grazer taxa, but no effect of the algal host. This suggests that grazer-specific foraging is more important in driving the qualitative range of feeding in the consumer assemblage than host diversity per se within a macrohabitat, such as a bay or a lagoon. The stable isotope ratios of the mesoherbivores were in line with expectations based on the known feeding ecology of the grazers. However, the trophic diversity suggested by stable isotope analysis implies that even an established concept such as the mesograzer guild may encompass simplifications in terms of functional group membership.